Wanderer: An Aisthetic Inquiry into the Experience of Exile. - Shan, Summer (School of Art and Design, AUT, 2025)
This practice-led, artistic research project asks: If a sensory designer draws on a historical literary convention of the羁旅 (exile), how might she create fictional artefacts that speak to the experience of loss and disorientation experienced by a Chinese student studying overseas? The project tells the story of Jiang Xiazheng, and her experience of exile when living as a Chinese student overseas. At the center of the study is a fictional 旅行皮箱 (suitcase-portmanteau) that constitutes a repository of ephemera. This suitcase operates as a form of narrative portrait. Each artefact inside it is a fictional design (including the student’s passport, official documents, and assignments she submitted for assessment). In composite these relate a story of estrangement and eventual triumph. Jiang Xiazheng’s background narrative is available in a small bound notebook (on the shelf). On the table beside the suitcase is her final degree project. The suitcase has two layers. Please feel free to unpack and examine each artefact and return it to its original position. When you read, touch, smell and feel the objects, they will speak of an extraordinary experience in the language of aisthetic (sensory) design.